The Influence of Transformational Leadership The Principal's Influence on Teacher Performance Motivation Improvement: A Systematic Literature Review - Aini Septia Rahmalita; Dewi Sumiyarsih Syam; Rusdinal; Nurhizrah Gistituati; Anisah (Mudir: Jurnal Manajemen Pendidikan, 2025)
The problem of low teacher competence as reflected in the results of the Teacher Competency Test has a direct impact on the quality of learning. One of the factors that can influence the improvement of teacher performance is achievement motivation, which is influenced by the principal's leadership style. This study aims to examine the influence of transformational leadership on teacher achievement motivation through a systematic literature review approach. The method used is a literature review by analyzing articles from 2020-2025 obtained through Google Scholar and has gone through a peer-review process. The analysis was conducted using thematic synthesis on eleven articles that met the inclusion criteria. The results showed that transformational leadership characterized by idealized influence, inspirational motivation, intellectual stimulation, and individual attention significantly boosted teachers' achievement motivation. This leadership strategy is proven to create a supportive work environment, motivate teachers to develop their competencies and increase dedication to professional duties. This study makes an important contribution to education management by confirming that the implementation of transformational leadership is key in promoting teacher quality and education as a whole.